AN ANALYSIS OF ADJUNCT IN THE STORY OF A MOTHER BY HANS CHRISTIAN ANDERSEN - Latifah, Durotul; Aryani, Luh; Fortuna, Paramita Dewi (Faculty of Education and Teachers Training, 2024)
There are just few studies yielded the type meaning of adjunct. The study deals with the use of various meanings of adjuncts in the story by Hans Christian Andersen entitled “The Story of a Mother”. It aims to analyse the most dominant meaning’s type of adjunct used in the story. In analysing the short story, the researchers implement descriptive quantitative technique. The finding shows that the most dominant type of adjunct used is adjunct of place, followed by adjunct of manner, adjunct of time, adjunct of reason, frequency, and the last its adjunct of duration.